Reform of Inheritance Rights in Balinese Customary Law: Harmonizing Dharmaśāstra and Gender Justice - Manik Wedanti, I Gusti Ayu Jatiana (Jayapangus Press, 2025)
Balinese customary law as a living law system plays a crucial role in maintaining spiritual and social harmony among Balinese society. Inheritance regulations embedded in traditional awig-awig were initially patriarchal and often failed to accommodate the inheritance rights of women and adopted children. This study focuses on how the values of Dharmaśāstra are harmonized with the inheritance provisions of desa adat awig-awig in Bali, and to what extent this reformulation embodies substantive justice and the contemporary relevance of customary law. Employing a normative juridical method with statutory, conceptual, and case approaches, this research analyzes the revised awig-awig in Kerobokan, Sidemen, and Gunaksa. The findings reveal a significant transformation, acknowledging women’s and adopted children’s inheritance rights through the spiritual principle of adhikāra and the reinterpretation of putrikā and dattaka concepts. Such reformulation not only strengthens substantive justice but also upholds the sacred values of Dharma. The study recommends inclusive involvement of customary communities and younger generations in reforming customary law to ensure alignment with the demands of contemporary justice, while preserving spiritual and cultural authenticity.This reformulation provides an important model for other customary legal systems in Indonesia to achieve harmony between tradition and modern legal principles, and contributes practically by offering a framework for inclusive and adaptive customary law development at the national level.